Engineered Microvasculature in PDMS Networks Using Endothelial Cells Derived from Human Induced Pluripotent Stem Cells. Issue 8 (August 2017) - Sivarapatna, Amogh; Ghaedi, Mahboobe; Xiao, Yang; Han, Edward; Aryal, Binod; Zhou, Jing; Fernandez-Hernando, Carlos; Qyang, Yibing; Hirschi, Karen K.; Niklason, Laura E.
In this study, we used a polydimethylsiloxane (PDMS)-based platform for the generation of intact, perfusion-competent microvascular networks in vitro. COMSOL Multiphysics, a finite-element analysis and simulation software package, was used to obtain simulated velocity, pressure, and shear stress profiles. Transgene-free human induced pluripotent stem cells (hiPSCs) were differentiated into partially arterialized endothelial cells (hiPSC-ECs) in 5 d under completely chemically defined conditions, using the small molecule glycogen synthase kinase 3β inhibitor CHIR99021 and were thoroughly characterized for functionality and arterial-like marker expression. These cells, along with primary human umbilical vein endothelial cells (HUVECs), were seeded in the PDMS system to generate microvascular networks that were subjected to shear stress. Engineered microvessels had patent lumens and expressed VE-cadherin along their periphery. Shear stress caused by flowing medium increased the secretion of nitric oxide and caused endothelial cells s to align and to redistribute actin filaments parallel to the direction of the laminar flow. Shear stress also caused significant increases in gene expression for arterial markers Notch1 and EphrinB2 as well as antithrombotic markers Kruppel-like factor 2 (KLF-2)/4. These changes in response to shear stress in the microvascular platform were observed in hiPSC-EC microvessels but not in microvessels that were derived from HUVECs, which indicated that hiPSC-ECs may be more plastic in modulating their phenotype under flow than are HUVECs. Taken together, we demonstrate the feasibly of generating intact, engineered microvessels in vitro, which replicate some of the key biological features of native microvessels.